Vocabulary in practice, part 1 & 2 : 60 units of self-study vocabulary exercises with tests - Pye, Glennis (New Delhi : Foundation Books, Cambridge University Press, 2004)
Offering plenty of practice for vocabulary learners, these small and easy-to-carry books are ideal for busy people to use outside the classroom. All the words have been chosen using the Cambridge International Corpus to ensure that students learn the most widely used vocabulary. Includes regular tests and helpful word lists. This is Level 3/Pre-intermediate.
Keywords: Vocabulary -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; English language -- Self-instruction.